2021
DOI: 10.1002/ctm2.417
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‐specific ATGL ablation reduces burn injury‐induced metabolic derangements in mice

Abstract: Hypermetabolism following severe burn injuries is associated with adipocyte dysfunction, elevated beige adipocyte formation, and increased energy expenditure. The resulting catabolism of adipose leads to detrimental sequelae such as fatty liver, increased risk of infections, sepsis, and even death. While the phenomenon of pathological white adipose tissue (WAT) browning is well‐documented in cachexia and burn models, the molecular mechanisms are essentially unknown. Here, we report that adipose triglyceride li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…Studies in mice suggest that inhibition of ATGL can counteract the unwanted loss of adipose tissues in cancer cachexia and Berardinelli–Seip congenital lipodystrophy (BSCL2) . A very recent study investigated the role of ATGL in the recovery from severe burn injury in mice, which causes hypermetabolism, WAT loss, and ectopic lipid accumulation . These metabolic alterations are a hallmark of severe burn contributing to poor outcomes in humans .…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Studies in mice suggest that inhibition of ATGL can counteract the unwanted loss of adipose tissues in cancer cachexia and Berardinelli–Seip congenital lipodystrophy (BSCL2) . A very recent study investigated the role of ATGL in the recovery from severe burn injury in mice, which causes hypermetabolism, WAT loss, and ectopic lipid accumulation . These metabolic alterations are a hallmark of severe burn contributing to poor outcomes in humans .…”
Section: Introductionsupporting
confidence: 53%
“… 22 A very recent study investigated the role of ATGL in the recovery from severe burn injury in mice, which causes hypermetabolism, WAT loss, and ectopic lipid accumulation. 23 These metabolic alterations are a hallmark of severe burn contributing to poor outcomes in humans. 24 Notably, adipose tissue-specific deletion of ATGL and Atglistatin treatment reduced circulating FAs, ectopic lipid deposition, WAT browning, and liver dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…77,78 Previous studies showed that liver-specific ATGL deficiency improved glucose tolerance by increasing hepatic glucose utilisation and reducing hepatic glucose output without reducing hepatic steatosis. 79,80 However, the use of atglistatin, a chemical inhibitor of ATGL, in mice fed a high-fat diet reduced adipose tissue lipolysis, leading to a reduction in FA flux from the adipose tissue to the liver. 81 This was accompanied by a decrease in liver steatosis due to reduced expression of the genes involved in lipid uptake, storage, and de novo lipogenesis.…”
Section: Lipid Droplet Lipolysis and Autophagymentioning
confidence: 99%
“…The implications of browning are generally considered protective in the setting of obesity, as brite adipocytes increase energy expenditure by increasing fatty acid oxidation ( Barquissau et al, 2016 ) and improve insulin sensitivity. However, in the context of energy wasting and hypermetabolic states as cachexia ( Tamucci et al, 2018 ) or burns ( Kaur et al, 2021 ) these effects might not be favorable and therefore aggravate the disease. The mice used in this study were lean C57Bl/6J mice.…”
Section: Discussionmentioning
confidence: 99%